PELAYANAN KESEHATAN MASYARAKAT DAN HEWAN UNTUK PENCEGAHAN PENYAKIT VIRUS CORONA-19 (COVID-19) DAN FLU BURUNG DI PASAR BURUNG SATRIA KOTA DENPASAR - M. Wirapartha; G.A.M.K. Dewi; A.T. Umiarti; W. Wijana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
In the era of the Covid-19 pandemic, people are asked to continue to implement health protocols, use masks, wash hands regularly, maintain distance between people, and avoid crowds. The Satria Bird Market in Denpasar City is one of the animal markets located in the Denpasar area and it is still crowded with people. This poses a high risk of Covid-19 transmission because the market is always crowded and crowds generally occur, so strict precautions need to be taken to prevent Covid-19 transmission at the Satria Bird Market. The corona-19 virus is very dangerous to human health. Likewise, avian influnza virus which is an animal disease. Avian invluenza is not only dangerous for poultry, but also humans because it is zoonoses. This community service activity aims to prevent Covid-19 and afian influenza at the Satria Bird Market. This service activity was carried out in the form of distributing 1,250 pcs of masks, giving 1,800 chicken eggs, distributing 800 vitamin C + Zinc capsules to traders and parking attendants, disinfectant assistance, disinfecting stalls in the Satria Bird Market area of Denpasar City, and giving 400 Vitachick sachets for birds/poultry. This service was held on July 30, 2021, attended offline by 4 community service teams, 1 employee, 44 online lecturers, 2 bird market stall owners representatives, Satria bird market stall, and 3 parking attendants. Keywords: covid-19, avian influenza, nutrition, satria bird market, disease prevention